Evolutionary modeling and analysis of opinion exchange and epidemic spread among individuals - Zeng, Rong; Chang, Xinghua; Liu, Bo (Frontiers in Physics, 2024)
The opinions of individuals within a group about an ongoing epidemic play a crucial role in the dynamics of epidemic spread. People’s acceptance of others' opinions also changes with the changing epidemic situation and the dynamics of communication between individuals, how individuals' opinions and acceptance of others' views on epidemics affect the spread of epidemics has become an unresolved issue. In this study, we construct a two-layer coupled network that integrates the Hegselmann-Krause (HK) continuous opinion model with an epidemic model. This framework takes into account the evolutionary game of opinion acceptance among individuals within the group. We investigate the dynamic interaction between opinion exchange among individuals and the spread of the epidemic and derive the epidemic spread threshold of the model using the Quasi-Mean-Field (QMF) approach. The results indicate that under different infection rates, individuals in the group spontaneously form varying levels of opinion about the epidemic, which in turn evolve into different final infection states for the group. The higher the infection rate, the faster a positive and unified opinion forms. Promoting communication among individuals within the group can, to some extent, inhibit the spread of the epidemic. However, due to the diversity and complexity of information in the real world, the phenomenon of “delayed epidemic prevention” often occurs.